2018
DOI: 10.1186/s13071-018-2818-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of protein interactions between Eimeria maxima sporozoites and chicken jejunal epithelial cells by shotgun LC-MS/MS

Abstract: BackgroundEimeria maxima initiates infection by invading the jejunal epithelial cells of chicken. However, the proteins involved in invasion remain unknown. The research of the molecules that participate in the interactions between E. maxima sporozoites and host target cells will fill a gap in our understanding of the invasion system of this parasitic pathogen.MethodsIn the present study, chicken jejunal epithelial cells were isolated and cultured in vitro. Western blot was employed to analyze the soluble prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Although many invasion-related molecules of Eimeria have been studied [13,25], there are only a few reports concerning sporozoite receptors on host epithelia. In the current study, a cDNA library of chicken duodenal epithelial cells was constructed and screened for EaMIC3 receptor molecules by YTH.…”
Section: Discussionmentioning
confidence: 99%
“…Although many invasion-related molecules of Eimeria have been studied [13,25], there are only a few reports concerning sporozoite receptors on host epithelia. In the current study, a cDNA library of chicken duodenal epithelial cells was constructed and screened for EaMIC3 receptor molecules by YTH.…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectrometer was operated in MS/MS mode scanning from 380 to 1800 amu. The top 20 multiply charged ions were selected from each scan for MS/MS analysis ([36] #1323). Then, the MS/MS spectra were searched using MASCOT 2.2 (Matrix Science, London, UK), and the protein was identified by searching the B .…”
Section: Methodsmentioning
confidence: 99%
“…The gels were silver stained (Supplementary Figure 1), silver stained results showed that there were no distinct bands of specificity, therefore the whole strip was removed for mass spectrometry and analyzed. The proteins were subject to blast analysis by shotgun, then compared using the UniProt database (Huang et al, 2018).…”
Section: Screening Of Proteins Interacting Withmentioning
confidence: 99%